2020
DOI: 10.1021/acs.jchemed.0c00333
|View full text |Cite
|
Sign up to set email alerts
|

Developing and Implementing a Low-Cost, Portable Pedagogical Kit to Foster Students’ Water Quality Awareness and Engagement by Sampling Coastal Waters and Analyzing Physicochemical Properties

Abstract: Contextualized and socially relevant hands-on activities are an effective way to promote students’ involvement in the construction of knowledge. Considering the UN’s 2030 Agenda for Sustainable Development, the preservation of water resources is crucial for the sustainable development of a country. Therefore, the PVC project was implemented in the context of water quality monitoring. There were 440 students and 9 chemistry teachers involved. A low-cost portable pedagogical kit was developed in order to determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 14 publications
1
13
0
3
Order By: Relevance
“…A similar study has been published as a laboratory experiment focussed on analysing water quality. [21] Through direct observation and student interviews, the authors found similar learning benefits to those described by Rowe and co-workers. [20] While we have provided some specific examples in the area of chemistry, there are few published examples reported.…”
Section: Introductionsupporting
confidence: 65%
“…A similar study has been published as a laboratory experiment focussed on analysing water quality. [21] Through direct observation and student interviews, the authors found similar learning benefits to those described by Rowe and co-workers. [20] While we have provided some specific examples in the area of chemistry, there are few published examples reported.…”
Section: Introductionsupporting
confidence: 65%
“…2. the sampling of coastal waters and polluting plastics from beaches, and analysing the collected waters' physicochemical parameters (pH, temperature, turbidity, percentage of dissolved oxygen, salinity, and concentration of nitrates and nitrites), as well as the qualitative identification of (micro)plastics, using pedagogical kits (Araújo et al, 2020) specifically developed for the purpose, to promote the learning of chemistry curriculum contents related to the project (Araújo et al, 2021); and…”
Section: Promoting Citizen Science In Chemistry Teaching Through Pvc ...mentioning
confidence: 99%
“…The project consisted in monitoring coastal waters and marine litter quality in the North Coastal region of Portugal, thus explaining the role of Chemistry in society and its contribution to mitigate environmental issues. Considering the guidelines of the United Nations Agenda 2030 for Sustainable Development (United Nations, 2021a) and the United Nations Decade of Ocean Science for ISSN 1648-3898 /Print/ ISSN 2538-7138 /Online/ Sustainable Development (United Nations, 2021b), as well as the social and scientific relevance of the subject (Li et al, 2020;Mercogliano et al, 2020;Uddin et al, 2020;Wang et al, 2019;Wang et al, 2020;Zhang & Chen, 2020), it was considered consistent that marine litter and coastal water quality context, specifically water contamination by plastics and microplastics, would be explored within the PVC project (Araújo et al, 2020a). The PVC project actively engaged students in four main stages:…”
Section: The Pvc Citizen Science Projectmentioning
confidence: 99%